Partial characterization of cyclodextrin glucanotransferase by Bacillus sp. TS1-1 - Ummi Nor Husna, Husin (2009)
The crude culture that contains cyclodextrin glucanotransferase (CGTase; EC 2.4.1.19) from Bacillus sp. TS1-1 has been partially purified by centrifugation and cross-flow filtration. Initial 242.74 U/ml of CGTase was detected in the culture after 24 hours of incubation. The crude supernatant obtained after centrifugation for 5000rpm, 5 minutes and 4oC was subsequently filtered at 15oC through cross-flow filtration using Kvick Lab cross-flow system. Two cassettes were used with molecular weight cut off of 50K and 10K. The retentate from 50K cassette was further filtered through 10K cassette. Each permeate and retentate from each cassette were tested for CGTase activity. Using cross-flow filtration, the crude enzyme was purified 2.33 fold. The crude and partially purified enzyme was then subjected to gel electrophoresis (SDS-PAGE) to determine the enzyme molecular weight. The partial purified enzyme especially at retentate 50K suggested an initial size of CGTase between 46 to 88 kDa. The crude and partial purified CGTase was then assayed using phenolpthalein method with slight modification for the determination of CGTase optimum pH, pH stability, optimum temperature and thermal stability. Based on this work, the optimum temperature for activity was at 40oC and 80oC, the thermal stability was from 40-70oC and from 60-90oC; the optimum pH for activity was at pH6 and pH10; the pH stability was from pH4 to 6.